The Yankee tea-party : or, Boston in 1773 - Watson, Henry C. (Henry Clay), 1831-1869 (Young American's library., 2012)
A fantastic account of the famous 'Boston Tea Party' when, in 1773, colonists in Boston protested the East India Company's stranglehold on the tea import market by throwing three shiploads of tea into the sea, and the events that followed.